Protocol for Extractions in Orthodontia (2014)
Tooth extraction due to the need for space for orthodontic treatment in many cases causes changes in the alveolar ridge, which can result in functional and aesthetic problems for the successful completion of treatment stemming from an insufficient amou- nt of bone tissue. This problem requires the specialist to analyze each individual clinical situation and consider a number of factors specific to the patient, the treatment and the professional to whom they are referred, who will then determine the appropriate time to perform extractions. The purpose of this article is to describe post-extraction changes in the tooth socket and suggest a protocol that is appropriate for defining when and how best to carry out tooth extractions in orthodontic patients.